The Effectiveness of Educaplay Interactive Media on Mathematics Learning Outcomes of First Grade Students - Kireyna Chivi Sahditarani; Honest Ummi Kaltsum (FKIP - Universitas Riau, 2026)
This study aims to analyze the effectiveness of Educaplay interactive media on the Mathematics learning outcomes of first-grade students at SDN Karanganyar 1. The background of this study is the low understanding of students' mathematical concepts due to conventional learning that is less interesting and has not been integrated with technology. The research method used is a quantitative approach with a pre-experimental one group pretest–posttest design. The research subjects were 27 students who were given a pretest to measure initial abilities, then received treatment in the form of learning using Educaplay media, and then a posttest to measure improvements in learning outcomes. Data were collected through observation, testing, and documentation, then analyzed using a normality test and a paired sample t-test with a significance level of 0.05. The results showed an increase in the average score from 73.9 in the pretest to 82.9 in the posttest. The paired sample t-test produced a Sig. Value (2-tailed) of 0.000 <0.05 indicating a significant difference between the scores before and after treatment. Thus, Educaplay interactive media has been proven effective in improving students' learning outcomes in mathematical arithmetic operations and is able to encourage active involvement and students' learning motivation.